Sensors and mobile interfaces for stress level monitoring in people with diabetes - Ribeiro, G.; Postolache, O. (2021 12th International Symposium on Advanced Topics in Electrical Engineering (ATEE), 2021)
Stress is a natural feeling of not being able to cope with specific demands and events. The stress can become a chronic condition if a person does not take measures to manage it. Several stress meters have been proposed over the years, however still a reduced number of variables were considered mainly the skin conductivity and/or heart rate. Additional variables can be considered such as respiratory rate can be relevant to the estimation of stress level. In this paper, a prototype to measure and predict the stress levels is presented together preliminary experimental values. Moreover, a mobile application was also developed for users' stress assessment.